Theiler’s virus-induced demyelinating disease as an infectious model of progressive multiple sclerosis - Pike, Steven C.; Welsh, Nora; Linzey, Michael; Gilli, Francesca (Frontiers in Molecular Neuroscience, 2022)
Multiple sclerosis (MS) is a neuroinflammatory and neurodegenerative disease of unknown etiology. However, several studies suggest that infectious agents, e.g., Human Herpes Viruses (HHV), may be involved in triggering the disease. Molecular mimicry, bystander effect, and epitope spreading are three mechanisms that can initiate immunoreactivity leading to CNS autoimmunity in MS. Theiler’s murine encephalomyelitis virus (TMEV)-induced demyelinating disease (TMEV-IDD) is a pre-clinical model of MS in which intracerebral inoculation of TMEV results in a CNS autoimmune disease that causes demyelination, neuroaxonal damage, and progressive clinical disability. Given the spectra of different murine models used to study MS, this review highlights why TMEV-IDD represents a valuable tool for testing the viral hypotheses of MS. We initially describe how the main mechanisms of CNS autoimmunity have been identified across both MS and TMEV-IDD etiology. Next, we discuss how adaptive, innate, and CNS resident immune cells contribute to TMEV-IDD immunopathology and how this relates to MS. Lastly, we highlight the sexual dimorphism observed in TMEV-IDD and MS and how this may be tied to sexually dimorphic responses to viral infections. In summary, TMEV-IDD is an underutilized murine model that recapitulates many unique aspects of MS; as we learn more about the nature of viral infections in MS, TMEV-IDD will be critical in testing the future therapeutics that aim to intervene with disease onset and progression.